2007
DOI: 10.1042/bst0351119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of inflammatory neurodegeneration: iNOS and NADPH oxidase

Abstract: Inflammation contributes to a wide variety of brain pathologies, apparently via glia killing neurons. A number of mechanisms by which inflammatory-activated microglia and astrocytes kill neurons have been identified in culture. These include iNOS (inducible nitric oxide synthase), which is expressed in glia only during inflammation, and PHOX (phagocytic NADPH oxidase) found in microglia and acutely activated by inflammation. High levels of iNOS expression in glia cause (i) NO (nitric oxide) inhibition of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(182 citation statements)
references
References 42 publications
5
173
1
3
Order By: Relevance
“…The observations suggesting that the effects of hMSCs were mediated through microglia and/or macrophages are consistent with indications that both microglia and macrophages can be alternatively activated to play contrasting roles in response to injury (33)(34)(35). The increases in Gal-3 and Ym1 observed here provided a direct link between the effects of the hMSCs and activation of microglia or macrophages that may have been produced either by paracrines secreted by the hMSCs or by direct cell-to-cell contacts, as was observed during immunosuppression of T cells by MSCs (27).…”
Section: Discussionsupporting
confidence: 61%
“…The observations suggesting that the effects of hMSCs were mediated through microglia and/or macrophages are consistent with indications that both microglia and macrophages can be alternatively activated to play contrasting roles in response to injury (33)(34)(35). The increases in Gal-3 and Ym1 observed here provided a direct link between the effects of the hMSCs and activation of microglia or macrophages that may have been produced either by paracrines secreted by the hMSCs or by direct cell-to-cell contacts, as was observed during immunosuppression of T cells by MSCs (27).…”
Section: Discussionsupporting
confidence: 61%
“…Microglia are brain macrophages that produce oxidants and induce expression of iNOS if they detect pathogens or damage (Brown, 2007). This study showed non significant alteration in brain lipid peroxidation, consequently no brain damage.…”
Section: Discussionmentioning
confidence: 79%
“…Activated microglia, via production of peroxynitrite and various pro-inflammatory cytokines and prostanoids, are suspected to contribute to the pathogenesis of many neurodegenerative disorders (Brown 2007). In light of the anti-inflammatory potential of AMPK as noted above, it is reasonable to suspect that AMPK activation might be protective in this regard, and indeed, several studies demonstrate that AMPK activators can exert antiinflammatory effects on cultured microglia.…”
Section: Preventing Neurodegenerative Disordersmentioning
confidence: 99%